A autonomia do direito à proteção dos dados pessoais: uma perspectiva multinível e dialógica - Carvalho, Bruno Vinícius Stoppa (2023)
The technological revolution implies new risks for individuals and traditional legal institutes such as privacy protection are no longer able to solve all the possible consequences that the processing of personal data can cause to the individual, so it is necessary to recognize the autonomy of such a right. In addition, the flow of information in the globalized economy also poses a challenge to the protection of personal data based solely on local legal systems. To this extent, by making explicit the autonomy of personal data protection as a fundamental right, Constitutional Amendment 115/22 must be interpreted from a multilevel perspective, adding the protective standards of the inter-American global and regional system in comparison with the local order in order to confer maximum protective effectiveness to the individual. Based on bibliographical, normative and jurisprudential research, including international research, the content of the right to the protection of personal data in the UN system, in the inter-American regional system and in the national legal system is presented. The methodology adopted makes it possible to identify the global, regional and local standards that must be harmonized by the interpreter in order to provide the highest level of protection to the individual, from the perspective of multilevel constitutionalism. The present dissertation densifes the content of the protection of personal data as an autonomous fundamental right from the multilevel dialogue, from the perspective of human rights and from the jurisprudence of the Brazilian Federal Supreme Court